Utilization of BIM in the construction of a submarine tunnel: a case study in Xiamen city, China - Li, Sai; Zhang, Zhongjian; Mei, Gang; Lin, Daming; Yu, Jin; Qiu, Renke; Su, Xingju; Lin, Xuechun; Lou, Chonghua (Journal of Civil Engineering and Management, 2021)
Building information modeling (BIM) is an emerging technology that can effectively solve the problems of information dispersion, complex personnel management, and lack of construction supervision, which often occur during the construction of tunnel engineering. Taking the construction of Haicang Tunnel in Xiamen, China as a case study, the utilization of BIM technology in the design stage, the construction simulation and operation are demonstrated during the full-life cycle of the project. During the construction of Haicang Tunnel, the technologies of BIM 3D, BIM 4D, BIM 5D, and Cloud Platform are used to make the construction process controllable and to facilitate the implementation and deployment of construction plans. BIM 3D is a visualization method to show the detailed model in the construction. The design is optimized by the navigation collision function of BIM 3D. BIM 4D adds the time schedule into BIM 3D model to show the construction schedule. BIM 5D adds the cost into BIM 4D model to show the construction consumption. The methods of BIM 4D and BIM 5D can assist the engineering management in allocating resources and funds in the project. Cloud Platform is used to effectively implement information management.